Effects of structural characterizations on fragility functions of bridges subject to seismic shaking and lateral spreading - Zhang, Jian; Huo, Yili; Brandenberg, Scott J.; Kashighandi, Pirooz (Earthquake Engineering and Engineering Vibration, 2008)
This paper evaluates the seismic vulnerability of different classes of typical bridges in California when subjected to seismic shaking or liquefaction-induced lateral spreading. The detailed structural configurations in terms of superstructure type, connection, continuity at support and foundation type, etc. render different damage resistant capability. Six classes of bridges are established based on their anticipated failure mechanisms under earthquake shaking. The numerical models that are capable of simulating the complex soil-structure interaction effects, nonlinear behavior of columns and connections are developed for each bridge class. The dynamic responses are obtained using nonlinear time history analyses for a suite of 250 earthquake motions with increasing intensity. An equivalent static analysis procedure is also implemented to evaluate the vulnerability of the bridges when subjected to liquefaction-induced lateral spreading. Fragility functions for each bridge class are derived and compared for both seismic shaking (based on nonlinear dynamic analyses) and lateral spreading (based on equivalent static analyses) for different performance states. The study finds that the fragility functions due to either ground shaking or lateral spreading show significant correlation with the structural characterizations, but differences emerge for ground shaking and lateral spreading conditions. Structural properties that will mostly affect the bridges’ damage resistant capacity are also identified.